Kinetic study on alkylation of hydroquinone with methanol over SO3H functionalized Bronsted acidic ionic liquids - Bhongale, V. Priyanka; Amonkar, Amogh A.; Joshi, Sunil S.; Mali, Nilesh A. (Canadian Journal of Chemical Engineering, 2022)
O-alkylation of a dihydric phenol (i.e., hydroquinone) with methanol in presence of benzoquinone catalyzed by double SO3H functionalized Bronsted acidic ionic liquids (i.e., 1,3-disulphonic acid imidazolium hydrogen sulphate, 1,3-disulphonic acid benzimidazolium hydrogen sulphate, and sulphuric acid) is studied in a batch reactor. The sensitivity of activity and selectivity with reaction time, temperature, speed of agitation, and catalyst loading was examined. The plausible reaction pathways proposed based on the experimental observations and detailed kinetic investigation are performed by assuming a homogeneous reaction phase. The kinetic parameters, such as pre-exponential factor and activation energy, are estimated for both ionic liquids and sulphuric acid by considering all competitive reactions, and comparative results were presented. An extended form of the Arrhenius equation is used to estimate the kinetic parameters for the reaction which showed curvature in lnk against a 1/T plot. The model prediction with the estimated kinetic parameters is in good agreement with the experimental data, which confirmed the model validity in the experimental operating range. It was found that ionic liquid has a potential application in the synthesis of a selective monoalkylated product of hydroquinone. The kinetic analysis performed is found to be useful in the understanding of process behaviour.
Keywords: 4-Methoxyphenol; Hydroquinone; ionic liquids; Kinetic analysis; O-alkylation